Development of Multiple Real-Time Fluorescent Quantitative PCR for Vibrio Pathogen Detection in Aquaculture - Binzhe Zhang; Yulie Qiu; Chenxi Shi; Jian Zhang (Veterinary Sciences)
The Vibrio genus represents a critical group of bacterial pathogens in the marine environment globally, leading to massive mortality in the aquaculture industry. Diagnosing vibriosis, an infection caused by Vibrio species, in clinical samples poses challenges due to its non-specific clinical manifestations. In this study, we developed a TaqMan probe-based multiplex real-time PCR method for the simultaneous detection and quantification of four Vibrio pathogens: Vibrio anguillarum (Va), Vibrio alginolyticus (Val), Vibrio harveyi (Vh), and Vibrio scophthalmi (Vsc). The assay targets conserved intra-species regions and specific inter-species regions using specific primers and TaqMan probes to ensure specificity. Sensitivity analysis demonstrated that the multiplex real-time PCR assay could simultaneously detect the four different bacteria, with detection limits of 26–60 copies per reaction, making it 100 times more sensitive than conventional PCR assays. Additionally, the assay exhibited high reproducibility, with intra- and inter-group coefficients of variation below 1.4%. A total of 63 clinical samples was analyzed using this established assay, which successfully detected both single and mixed infections. These results demonstrate that the multiplex quantitative PCR assay is a rapid, specific, and sensitive diagnostic tool for the detection of Va, Val, Vh, and Vsc, making it suitable for monitoring these bacteria in both single- and co-infected clinical samples.